Attitudes of Administrators of Vocational Education Institutions in relation to certain Personal and Demographic Variables - Venkateswarlu , N.; Chandrasekhar , K. (INDIAN EDUCATIONAL REVIEW, 2009)
This paper presents an in-depth study of deficiencies, hurdles and conflicts in the existing system of vocational education in the state of Andhra Pradesh. The sample of the study comprised of 84 institutes, which consisted of 24 High Schools, 24 Junior Colleges, 24 Industrial Training Institutes and 12 Polytechnic Colleges and 100 Administrators. For knowing the attitude of administrators an attitude scale was developed by the investigators. A three stage stratified random sampling technique was used. The results of the study revealed that administrators are not happy with the prevailing situation in the field of vocational education. Further, a large number of subjects expressed their inclination to have a separate independent stream of vocational education instead of incorporating vocational courses in the institutions of general education. Hence, it is necessary that the government and the managements involved in the process of vocationalisation should plug the loopholes and eliminate the deficiencies so that ideal vocational education may be provided in tune with the demands of the present day society.